Teaching English Listening Comprehension Using The Flipped Instruction Model - Nindi Rika Riani; Nurdin Noni; Sukardi Weda (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2025)
This study investigated students’ difficulties and explore students’ perceptions regarding the use of the Flipped Learning Model in a junior high school English listening class. The study used a quantitative descriptive approach, utilizing two validated questionnaires: one to measure perceived difficulties and the other to assess students’ perceptions of the learning model. Participants were 24 eighth-grade students who were learning English listening with a Flipped Learning Model, where learning materials were accessed before class and class time was dedicated to interactive activities. The results revealed that the majority of students (99%) classified their experience with the Flipped Instruction Model as “Very Easy,” with a mean difficulty score of 34.00 out of 40. Students’ perceptions of the Flipped Instruction Model were overwhelmingly positive, with 50% classifying their attitudes as “Very Positive” and the remaining 50% as “Positive.” The mean perception score was 30.42 out of 40. Students particularly valued the preparation phase, reporting that studying the material before class made them feel more prepared, increased their independence, and increased their engagement during class discussions. Flexibility, easy access to resources, and opportunities for reflection and repetition were highlighted as key benefits. While most students felt supported by their teachers and peers, some expressed a need for more direct guidance during class sessions, suggesting that a balance between autonomy and scaffolding is important. These findings support the existing literature that the Flipped Learning Model can reduce cognitive and affective barriers to language learning by allowing repeated exposure to materials and fostering a supportive and interactive classroom environment. The structure of the model not only facilitates comprehension but also promotes motivation, self-directed learning, and metacognitive awareness among students. However, the study also noted the importance of addressing external factors such as the home learning environment to maximize the benefits of flipped learning. In conclusion, the Flipped Learning Model proved to be highly effective and well-received in the context of an English listening classroom for junior high school students. The model minimized perceived difficulty, increased student engagement and motivation, and was positively received by learners. These results suggest that the Flipped Learning Model is a feasible and promising strategy for improving listening comprehension and should be considered for wider implementation in language education.